Laser ultrasonic time-domain synthetic aperture focusing (SAFT) co-overlay software and hardware (COSH) computing system based on ZYNQ - Tan, Junfu; Ni, Chenyin; Wu, Chanjuan; Ying, Kaining; Dai, Lunan; Shen, Zhonghua (Frontiers in Materials, 2024)
Co-Overlay Software and Hardware (SAFT-COSH) method based on the ZYNQ software and hardware cooperative architecture is designed for the algorithm of laser ultrasonic Time-Domain Synthetic Aperture Focusing Technique based on Delay and Sum ( DAS-SAFT) of signals. By employing optimizations such as loop unrolling and pipeline design, the calculation efficiency of the method is further improved. The hardware as well as the algorithm is verified by applying data obtained in a laser ultrasonic test. It can be found that the result obtained by the SAFT-COSH method is similar to those obtained by other methods while it takes the least calculation time among all, moreover, the time consumption of the SAFT-COSH system is 1/28 of that of the I9-13900KF CPU used for DAS-SAFT calculation. Finally, it was found by analyzing the time consumption of the DAS-SAFT procedure that the calculation time of the SAFT-COSH system is short enough to support real-time 3D imaging. Characteristics of high efficiency and low cost in the SAFT-COSH method make it applicable in fields that require fast imaging using SAFT-based methods.